CD200 restrains macrophage attack on oligodendrocyte precursors via toll-like receptor 4 downregulation. Issue 4 (April 2016) - Hayakawa, Kazuhide; Pham, Loc-Duyen D; Seo, Ji Hae; Miyamoto, Nobukazu; Maki, Takakuni; Terasaki, Yasukazu; Sakadžić, Sava; Boas, David; van Leyen, Klaus; Waeber, Christian; Kim, Kyu-Won; Arai, Ken; et al.
There are numerous barriers to white matter repair after central nervous system injury and the underlying mechanisms remain to be fully understood. In this study, we propose the hypothesis that inflammatory macrophages in damaged white matter attack oligodendrocyte precursor cells via toll-like receptor 4 signaling thus interfering with this endogenous progenitor recovery mechanism. Primary cell culture experiments demonstrate that peritoneal macrophages can attack and digest oligodendrocyte precursor cells via toll-like receptor 4 signaling, and this phagocytosis of oligodendrocyte precursor cells can be inhibited by using CD200-Fc to downregulate toll-like receptor 4. In an in vivo model of white matter ischemia induced by endothelin-1, treatment with CD200-Fc suppressed toll-like receptor 4 expression in peripherally circulating macrophages, thus restraining macrophage phagocytosis of oligodendrocyte precursor cells and leading to improved myelination. Taken together, these findings suggest that deleterious macrophage effects may occur after white matter ischemia, whereby macrophages attack oligodendrocyte precursor cells and interfere with endogenous recovery responses. Targeting this pathway with CD200 may offer a novel therapeutic approach to amplify endogenous oligodendrocyte precursor cell-mediated repair of white matter damage in mammalian brain.